The effect flammability limit in conventional combustion of hydrogen enrichment in natural gas - Nur Syuhada, Mohd Shokri (2009)
The use of hydrogenated fuels shows considerable promise for applications in gas turbines and internal combustion engines. The aims of this study are to determine the flammability limits of natural gas/ air and to investigate the effect on flammability limit of natural gas/ air enriched up to 60% hydrogen of fuel by volume at atmospheric pressure and ambient temperature. The experiments were performed in a 20 L closed explosion vessel. The mixtures were ignited by using spark permanent wire that placed at the centre of the vessel. The pressure-time variations during explosions of natural gas/air mixtures in explosion vessel were recorded. The explosion pressure data is used to determine the flammability limit which flame propagation is considered occurred if explosion pressure greater than 0.1 bar. In this study, the result shows the flammability limits is from 6 vol% to 15 vol% of natural gas and have revealed that the addition of hydrogen in natural gas extends the lower flammability limit initially 6 vol% to 2 vol% of methane.